1989
DOI: 10.1210/endo-125-2-730
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Formation Is Prevented by Administration of Verapamil to Diabetic Rats*

Abstract: The purpose of the present study was to examine the effects on cataractogenesis of daily sc administration of the Ca2+ antagonist drug verapamil to diabetic rats. Streptozotocin-induced diabetic rats were given verapamil half-way through the 8-week experimental period or during the full 8 weeks of diabetes. Verapamil administration had no effect on the high blood glucose values, low circulating insulin levels, or elevated triglyceride and cholesterol concentrations in the diabetic rats. Untreated diabetic rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
0
19
1
2
Order By: Relevance
“…The concentration of verapamil we adopted has been shown to reduce the incidence of diabetic cataracts measured after 8 weeks of hyperglycemia from 90% to 20% in a previous study (20). However, in the present study, verapamil failed to prevent significantly the onset and progression of diabetic cataracts.…”
Section: +contrasting
confidence: 79%
See 3 more Smart Citations
“…The concentration of verapamil we adopted has been shown to reduce the incidence of diabetic cataracts measured after 8 weeks of hyperglycemia from 90% to 20% in a previous study (20). However, in the present study, verapamil failed to prevent significantly the onset and progression of diabetic cataracts.…”
Section: +contrasting
confidence: 79%
“…Previous studies have demonstrated that verapamil exerts an inhibitory effect on diabetic cataracts in rats (20,22,23). The concentration of verapamil we adopted has been shown to reduce the incidence of diabetic cataracts measured after 8 weeks of hyperglycemia from 90% to 20% in a previous study (20).…”
Section: +mentioning
confidence: 84%
See 2 more Smart Citations
“…However, it has also been stated that a breakdown in phosphoinositide metabolism destroys the structure of the lens, which in turn leads to cataract formation [4]. Recent research efforts have focused on lens electrolyte imbalances in diabetic cataract [5]. We have analyzed the ion alterations in diabetic rats and the effects of the Ca channel blocker verapamil.…”
Section: Introductionmentioning
confidence: 99%